Effectiveness of the application of resonant magnetoquantum therapy in complex restorative treatment of patients who have had ischemic stroke - I. P. Shmakova; V. V. Teschuk (Kazimierz Wielki University, 2018)
The effectiveness of the application of RMQT in addition to drug therapy was studied in 98 patients who had had IS at the early stage of rehabilitation. Based on the performed clinical, neurofunctional, biochemical studies, life quality assessment, there were established the features of the action of RMQT at the stage of early rehabilitation on the pathological and sanogenetic mechanisms in the patients having had IS: improvement of the state of cerebral hemodynamics; brain electrogenesis; liquor dynamics; lipid metabolism, rheological properties of blood, which contributed to the regression of neurological symptoms, namely, an increase in the range of active motions and muscle strength, a reduction in the muscle tone, a decrease in the arterial pressure (AP), an improvement in cognitive, intellectual-mnetic functions. It has been established that the patients having had IS were characterized by subjective and neurological manifestations of the disease, changes in the functional state of the nervous system (disturbance of cognitive and intellectual-mnemonic functions, brain electrogenesis, liquor dynamics) and cardiovascular system, cerebral circulation (hyperperfusion in all vascular basins, asymmetry of the blood circulation, increase in the peripheral vascular resistance), biochemical indices and quality of life. It has been shown that the use of the RMQT complex by a multilevel method in addition to basic medical therapy of the patients who have had IS at the stage of early rehabilitation can reduce the subjective and neurological manifestations of the disease, improve cognitive and intellectual-mnestic functions, improve intracardiac hemodynamics, cerebral circulation through the main head vessels and intracranial arteries, which characterized by an increase in the linear velocity of blood circulation, decreased hyperperfusion, peripheral vascular resistance and their asymmetry. It allows to improve significantly bioelectric activity of the brain, liquor dynamics, rheological-coagulation properties of blood and lipid metabolism. The effectiveness of RMQT was obtained in the patients with IS in 3 weeks and significantly increased after 3 months. The effectiveness of the application of RMQT by a multilevel method facilitates the achievement of a fairly high quality of life of the patients who have had IS, followed by preservation of it for 3 and 6 months according to the indices of working capacity, general well-being, intellectual-mnestic functions, and social activity.